Clinical trials treating focal segmental glomerulosclerosis should measure patient quality of life - Gipson, Debbie S. (2010)
Optimal therapy of patients with steroid-resistant primary focal segmental glomerulosclerosis (FSGS) remains controversial. This report describes the initial study design, baseline characteristics, and quality of life of patients enrolled in the FSGS Clinical Trial, a large multicenter randomized study of this glomerulopathy comparing a 12-month regimen of cyclosporine to the combination of mycophenolate mofetil and oral dexamethasone. Patients with age ranging 2–40 years, with an estimated glomerular filtration rate >40 ml/min per 1.73 m(2), a first morning urine protein-to-creatinine ratio over one, and resistant to corticosteroids were eligible. The primary outcome was complete or partial remission of proteinuria over 52 weeks after randomization. In all, 192 patients were screened, of whom 138 were randomized for treatment. Ethnic distributions were 53 black, 78 white, and 7 other. By self- or parent-proxy reporting, 26 of the 138 patients were identified as Hispanic. The baseline glomerular filtration rate was 112.4 (76.5, 180.0) ml/min per 1.73 m(2), and urine protein was 4.0 (2.1, 5.3) g/g. Overall, the quality of life of the patients with FSGS was lower than healthy controls and similar to that of patients with end-stage renal disease. Thus, the impact of FSGS on quality of life is significant and this measurement should be included in all trials.